Text mining social media for competitive analysis - Germán Gémar; José Antonio Jiménez-Quintero (Tourism & Management Studies)
Social media are utilised widely. Companies increasingly use social media to communicate and interact with customers. Much information is thereby generated and is available to everybody, including competitors. Firms need to analyse what their customers say and interact with them. Using text mining tools, companies can know where they are in relation to their competitors and control the behaviour of these. Transforming text into data and data into knowledge can be vital to make the right decisions and improving the competitive strategy of companies. This study used a text mining tool to analyse the primary social media sites, including Twitter, Facebook, LinkedIn, YouTube and others, with a focus on a sample of hotels. The dimensions analysed were sentiments, passion and reach. A dependence was found between several variables obtained through text mining and financial performance. The results indicate that analysis of social media using th